NIOSOMES A PROMISSING NANOCARRIER: A REVIEW - BHANGE, MANJUSHA A.; PETHE, ANIL M.; JADHAV, AMRAPALI (International Journal of Applied Pharmaceutics, 2023)
There are numerous traditional methods for applying medications to the skin. Transdermal has become a popular method of drug delivery in recent years for a variety of medications that are difficult to administer in other ways. Transdermal drug delivery has a number of advantages, the most important of which is the prevention of first-pass metabolism and the stomach environment, which would render the drug inactive. In addition to discussing in depth the various formulation techniques and permeability enhancement for improved therapeutic efficacy, a transdermal patch allows for the controlled release of medication into the patient, typically through membrane pores that house a reserve of medication or over body heat that melts thin layers of medication entrenched in the adhesive. The drug molecules can permeate the skin and be administered in this manner. Niosomes are vesicles made of non-ionic surfactants that are more stable, biodegradable, and generally harmless. Because surfactants are more chemically stable than lipids, niosomes are ideal for liposomes. The main topics of this review study are the concept of niosome, its benefits and drawbacks, composition, various type of transdermal formulation, enhancers using in this delivery and novel transdermal drug delivery, variables influencing niosomes, characterization, and use of noisome. Niosomes can be used to carry both amphiphilic and lipophilic drugs. Niosomes have great potential in targeted drug delivery of anticancer and anti-infective agents. This review article represents the structure of Niosomes, its advantages and disadvantages, types of niosomes, applications, method of preparation of niosomes.